295 Awardee Talk: Novel regulation of growth hormone by kisspeptin. (5th December 2019) - Sartin, James; Daniel, Jay A; Foradori, Chad; Whitlock, Brian
Abstract: Kisspeptin (KP) is critical regulator of reproductive function through it's potent stimulation of gonadotropin releasing hormone (GnRH). In addition there has been inconclusive evidence to suggest intravenous KP can stimulate growth hormone (GH). Studies in 24 h fasted (but not fed) sheep determined that ICV injection of Kp-10 can increase plasma GH concentrations. This led to questions about the mechanism linking KP and GH. Since fasting is a critical requirement for the Kp effect on GH, studies were focused on factors that are linked to fasting within the hypothalamus and are known regulators of GH. Fasting causes a major upregulation of neuropeptide Y (NPY), a potent appetite regulator and in ruminants, a stimulator of GH. Pretreatment of BIBO 3304, an NPY receptor antagonist, blocked the effect of KP to increase GH and implicated NPY as a mediator of the KP effect. Indeed, KP injected ICV upregulated cFOS in NPY and GH Releasing Hormone (GHRH) cells in the arcuate nucleus and reduced cFOS in Somatostatin (SS) cells in the periventricular nucleus. Another factor, altered by fasting and capable of regulating GH, is Ghrelin. Both blockage of Ghrelin release and central blockade of Ghrelin receptors reduced or blocked release of GH after KP treatment. These experiments suggest an hypothesis that fasting upregulates central Ghrelin and NPY expression permitting the activation of NPY by KP. NPY in turn activates GHRH and inhibits SS to release GH.